Self-Assembled Micelles of Amphiphilic PEGylated Drugs for Cancer Treatment - Al-Amili, Majdi; Jin, Zhu; Wang, Zhongmin; Guo, Shengrong (Current Drug Targets, 2021)
Generally, poor solubility and imprecise delivery of chemotherapeutic drugs can compromise their efficacies for clinical cancer treatment. In order to address such concerns, poor water-soluble drugs are conjugated with poly(ethylene glycol) (PEG) to obtain PEGylated drugs, which have improved water solubility and can also self-assemble in an aqueous solution to form micelles (PEGylated drug micelles). The surface PEG layer enhances the micelles’ colloidal stability and reduces the interaction with physiological surroundings. Meanwhile, PEGylated drug micelles are tumor- targeting via the enhanced permeation and retention (EPR) effect to improve antitumor efficacy in comparison with free drugs. PEGylated drug micelles employ drugs as parts of the carrier medium, which increases the micelles’ drug loading capacity relatively. The development of stimuli- responsive PEGylated drug micelles facilitates the drug release to be smart and controllable. Moreover, the PEGylated drug micelles show great potentials in overcoming the challenges of cancer therapy, such as multidrug resistance (MDR), angiogenesis, immunosuppression, and so on. In this review, we highlight the research progresses of PEGylated drug micelles, including the structures and properties, smart stimuli-responsive PEGylated drug micelles, and the challenges that have been overcome by PEGylated drug micelles.
Keywords: Micelles